Features of mental health of citizens of Ukraine in the conditions of epidemic danger and reforming of health care system at the present stage - Tabachnikov Станіслав; Osuhovska Олена; Khaustova Олена; Martsinkovska Інна; Markov Артур; Salden Вікторія; Tovalovich Тетяна (Psychosomatic Medicine and General Practice, 2021)
Relevance. The global pandemic caused by the prevalence of COVID-19 (SARS-Cov-2) has become a trigger for the formation of a wide range of problems in the medical, socio-psychological, and rehabilitation spheres. The frequency of neurological or psychiatric diagnosis in patients after SARS-Cov-2, in the next 6 months, was 33.62%; the frequency of first diagnosis is 25.79%, and the mental health disorders themselves are diverse and affect almost all aspects of mental functioning, significantly worsening the quality of life. In addition, the extreme burden of the healthcare system in Ukraine in the context of a prolonged socio-economic and political crisis requires immediate реформування reform. Therefore, it is important to study the peculiarities of mental health of Ukrainian citizens in the context of epidemic danger and reform of the healthcare system at the present stage. Goal. To study the peculiarities of mental health of Ukrainian citizens in the paradigm of reforming the healthcare system in conditions of epidemic danger at the present stage. Materials and methods. Subject to informed consent in compliance with the principles of Bioethics and deontology, for the period from March to September 2021, 80 people aged 20 to 80 years were examined, who suffered covid-19 in 2020-2021 in mild (Group 1) and moderate severity – Group 2 (lung damage from 25 to 60%) and did not previously have a psychiatric diagnosis. The clinical and psychopathological method and screening diagnostics were implemented in the form of a semi-structured psychopathological interview, the main purpose of which was a comprehensive assessment of the patient’s mental status. The psychodiagnostic method was used using the hospital scale of anxiety and depression HADS; the quality of life questionnaire SF-36; Being Activity Mood (BAM); The scale of C. D. Spielberger – Yu.L. Khanin. Results. The most common mental and behavioral disorders (MBD) using the HADS method are analyzed. The results showed that clinically expressed anxiety occurred in 33.7% of respondents (groups 1 and 2), and its subclinical variant – in 6.3%. The dominant plot of anxiety was phobic thoughts, fears of severe or fatal consequences of a viral disease in yourself or your loved ones. Clinically expressed depression was observed in 29.7%, and subclinically – in 68%. Assessment of the quality of life according to the SF-36 questionnaire revealed clinical indicators of the average score on the "vital activity" scale – 32.0 and 43.0 in groups 1-2, respectively. According to the BAM methodology, the self-assessment of the individual indicated a low assessment of all indicators in both groups. 75% of patients on the C. D. Spielberger–Yu.L. Khanin scale had high levels of situational and personal anxiety, and 25% had moderate levels. The level of situational anxiety was 56.70±0.48, and personal anxiety – 43.86±0.34 points. The Law of Ukraine "On rehabilitation in the field of healthcare " and the resolution of the Cabinet of Ministers of Ukraine "Issues of Organization of rehabilitation in the field of healthcare" are legislative and executive innovations of the present, which differ: pronounced" patient-centricity"; stages; multi-level; multicomponent influences; a significant range of rehabilitation coverage; interdisciplinarity; consistency; organizational and informational integrity; management efficiency; modernity, innovation. That is, the implementation of this law, if the necessary funding is available, will provide rehabilitation assistance to the population of Ukraine, including in conditions of epidemic danger, at the proper level. Conclusions. Thus, according to our study, as a result of the covid-19 viral disease, there was an increase in the number of patients with MBD: adaptive, anxiety-phobic and depressive. Organizational and methodological aspects of comprehensive medical and psychological care for patients with MBD in the framework of the development of the corresponding algorithm included: unity of measures, manageability of impacts; integrality; holistic approach; continuity, etc. However, an algorithm should be developed and brought into line with the presented innovations of healthcare reform in Ukraine for the terminology and formation of rational, effective directed routing of patients with anxiety-phobic disorders in conditions of epidemic danger in order to improve and increase the level of medical and psychological care and improve their quality of life. Keywords: COVID-19 (SARS-Cov-2) pandemic, mental disorders, behavioral disorders, health system reform.